The Role of Leadership, Management, and Motivation in Indonesian Naval Officers' Performance - Agus Adriyanto (International Journal of Educational Narratives, 2024)
Background. In this research, the Indonesian National Navy principals have been chosen as unit analysis and 60 samples were purposive sampling. Purpose. The objective of this research is to know the effect of Leadership,  Management Skill, and Motivation to Performance of Indonesian navy officers. Method. Survey was applied in this research which data had been analyzed by path analysis after all variables put into a correlational matrix. Results. The result of the research shows that Performance of navy is effected directly by Leadership,  Management Skill, and Motivation. It is also found that Leadership is effected Motivation to Performance of navy directly. Based on those findings it could be concluded that any change or variation which occurred at Performance of navy might have been effected by Leadership,  Management Skill, and Motivation. Conclusion. Therefore, in Performance of navy, Leadership,  Management Skill, and Motivation should be put into strategic planning of human resources development.